IMPLEMENTASI PERATURAN DESA NOMOR 9 TAHUN 2024 TENTANG PENGELOLAAN SAMPAH DI DESA SAGULING KECAMATAN BAREGBEG KABUPATEN CIAMIS - Akmal Farizan; Sirodjul Munir; Regi Refian Garis (Nusantara Hasana Journal, 2026)
Waste management is essential for maintaining a clean and healthy environment. The village of Saguling has enacted Village Regulation No. 9 of 2024 on Waste Management. However, in its implementation, the Saguling Village Government has faced obstacles such as a lack of budget and land for the construction of a temporary waste disposal site, as well as low public awareness regarding waste management. This study aims to analyze the extent to which the implementation of Village Regulation No. 9 of 2024 on Waste Management in Saguling Village has been carried out. The research method used is qualitative descriptive, employing data collection techniques such as interviews, observation, and documentation, followed by data analysis techniques including data reduction, data presentation, and drawing conclusions. The research results indicate that the implementation of Village Regulation No. 9 of 2024 on Waste Management in Saguling Village has not yet been optimal. This is evident from the numerous indicators that remain suboptimal and technically hinder the Village Government in implementing waste management policies in Saguling Village. Despite facing obstacles in its implementation, the Saguling Village Government continues to work toward the successful implementation of waste management through public appeals, outreach, and engagement with the community.